The Preparation of Various New Heterocyclic Compounds via Cyclization of Substituted Derivatives of Phenacyl Esters of Hydrazonoacetic Acid - Mělnický, Radek; Grepl, Martin; Lyčka, Antonín; Bertolasi, Valerio; Kvapil, Lubomír; Dvořáková, Barbora; Hradil, Pavel (Synthesis, 2013)
A procedure for the preparation of derivatives of phenacyl hydrazonopropanoates and their application in the synthesis of various heterocycles has been developed. Not only is the preparation of indole derivatives described, but also a new method for the preparation of previously unknown pyridazine derivatives.
Keywords: phenacyl esters; hydrazone; cyclization; indoles; pyridazine